Alterations in platelet behavior after major trauma: adaptive or maladaptive?. (3rd April 2021) - Vulliamy, Paul; Kornblith, Lucy Z.; Kutcher, Matthew E.; Cohen, Mitchell J.; Brohi, Karim; Neal, Matthew D.
Abstract: Platelets are damage sentinels of the intravascular compartment, initiating and coordinating the primary response to tissue injury. Severe trauma and hemorrhage induce profound alterations in platelet behavior. During the acute post-injury phase, platelets develop a state of impaired ex vivo agonist responsiveness independent of platelet count, associated with systemic coagulopathy and mortality risk. In patients surviving the initial insult, platelets become hyper-responsive, associated with increased risk of thrombotic events. Beyond coagulation, platelets constitute part of a sterile inflammatory response to injury: both directly through release of immunomodulatory molecules, and indirectly through modifying behavior of innate leukocytes. Both procoagulant and proinflammatory aspects have implications for secondary organ injury and multiple-organ dysfunction syndromes. This review details our current understanding of adaptive and maladaptive alterations in platelet biology induced by severe trauma, mechanisms underlying these alterations, potential platelet-focused therapies, and existing knowledge gaps and their research implications.